Islamic Law in the Metaverse World: A Normative Study of Virtual Worship Practices and Transactions - Ahmad Rifai Yoga; Ahmad Yasin Dongoran; Arsyad Rizky Pratama Siregar; Nur Hafizah Husna; Rahmad Fauzi Hasibuan (Jurnal Sahabat ISNU SU, 2025)
The development of metaverse technology has presented new challenges in the application of Islamic law, particularly regarding worship practices and virtual transactions. The non-physical and interactive nature of the metaverse world demands a normative approach to assess the legal validity and legitimacy of various activities occurring within it. This study aims to examine how Islamic legal principles are applied in the context of virtual worship, such as online congregational prayer and digital marriage contracts, as well as digital asset-based economic transactions such as NFTs and cryptocurrencies. Using a juridical-normative approach and qualitative analysis, this study examines the relevance of Islamic jurisprudence (fiqh), maqasid sharia (the principles of sharia), and contemporary fatwas (religious edicts) in responding to the metaverse phenomenon. The results indicate that activities in the metaverse world are subject to Sharia law as long as they meet the principles of clarity (bayyinah), justice ('adl), and benefit (maslahah). Virtual space can be treated as a functional area of ​​Sharia law, as activities within it have real legal implications. This study recommends the importance of establishing a responsive and contextual digital Islamic legal framework to holistically address the dynamics of virtual space.